Business Risk, Financial Distress, and Investment Policy on Firm Value: A Case Study of PT Astra International Tbk - Dona Elvia Desi; Iin Sofya Randra; Tiara Lilis Surya; Faleria Putri Afrila (Dinasti Publisher, 2026)
This study aims to examine the effect of business risk, financial distress, and investment policy on firm value at PT Astra International Tbk during the period 2015-2024. Firm value in this study is measured using Price to Book Value (PBV), while business risk is measured by the Degree of Operating Leverage (DOL), financial distress by the Altman Z-Score,and investment policy by total asset growth (Asset Growth). The research employs an explanatory research design with a quantitative approach. Data analysis is conducted using descriptive statistics, classical assumption tests, and multiple regression analysis with the assistance of SPSS software. The results indicate that partially,only financial distress has a significant effect on firm value, whereas business risk and investment policy do not have a significant effect on firm value. However,simultaneously,business risk, financial distress, and investment policy have a significant effect on firm value. The coefficient of determination (adjusted R2) is 69.8%, indicating that these variables are able to explain 69.8% of the variation in firm value, while the remaining 30.2% is influenced by other factors outside the research model